Cross-sectional survey of barriers and opportunities for engaging backyard poultry producers and veterinarians in addressing poultry health. Issue 1 (2nd January 2023) - Greening, SS; Gates, MC
ABSTRACT: Aims: To assess the current level of engagement between backyard poultry keepers and veterinarians in New Zealand; to understand the opportunities and barriers for improving access to poultry health care; and to gauge the interest of backyard poultry keepers in participating in a voluntary national poultry health information system. Materials and methods: Backyard poultry were defined as any bird species kept for non-commercial purposes. Separate cross-sectional surveys were administered to backyard poultry keepers and veterinarians in New Zealand over 12-week periods starting 22 March 2021 and 03 May 2021 respectively. The veterinarian survey was advertised in the monthly update e-mail from the Veterinary Council of New Zealand, while the survey for backyard poultry keepers was advertised on various online platforms that focus on raising backyard poultry. Results for quantitative variables were reported as basic descriptive statistics, while qualitative free-text responses from open-ended questions were explored using thematic analysis. Results: A total of 125 backyard poultry keepers and 35 veterinarians completed the survey. Almost half (56/125; 44.8%) of backyard poultry keepers reported that they had never taken their birds to a veterinarian, with common reasons being difficulty finding a veterinarian, cost of treatment, and perceptions that most visits result in the bird being euthanised. The majority (113/125; 90.4%) of backyard poultry keepers reported that a general internet search was their primary source for poultry health advice. However, it remains unclear if owners were satisfied with the advice found online, as many cited that having access to reliable health information would be an incentive for registering with a poultry health information system. Of the veterinarian responses, 29/35 (82.9%) reported treating an increasing number of poultry in the last 5 years, although many (27/35; 77.1%) suggested they would be hesitant to increase their poultry caseload due to concerns over their lack of knowledge and confidence in poultry medicine; a lack of clinic resources to treat poultry; concerns over the cost-effectiveness of treatments; and a general feeling of helplessness when treating poultry, with most consultations being for end-stage disease and euthanasia. Conclusion: The results of this study highlight opportunities for increased engagement between backyard poultry keepers and veterinarians, including making available accurate poultry health information and providing veterinarians with improved training in poultry medicine. The results also support the development of a poultry health information system in New Zealand to further enhance health and welfare in backyard poultry populations. Abbreviations: MPI: Ministry for Primary Industries